Steel plate shear wall – a 20th century review - R. Vhatkar, Sudarshan; D. Jadhao, Pradip (International Journal of Engineering and Technology, 2018)
This paper provides a brief summary carried out in past analytical and experimental research work on steel plate shear walls with empha- sis given up to 20th Century. In buildings, two different systems exist to resists the loads viz., gravity load system and a lateral load sys- tem. To transfer the vertical loads to the footing gravity load system is used while lateral loads due to wind and seismic loads are resisted by the Lateral Load Resisting System (LLRS). Steel Plate Shear Walls (SPSW) is relatively a new type of LLRS; it has many distinct performance benefits including large displacement ductility capacities, high elastic stiffness properties, and stable hysteresis behavior as compared to other LLRS. The experimental results were also compared with simplified analytical models. The capacity of SPSW is li- mited to elastic buckling strength of its plate panels. This practice results not only in an undesirable one, but also in a conservative design, where columns buckle and may yield before the plate reaches a fraction of its capacity. With failure plate buckling is not synonymous and along its boundaries if plate is supported adequately, as in the case of SPSW the post buckling strength may be several times theoret- ical buckling strength.Â
Keywords: Diagonal Tension Field; Horizontal Boundary Element; Lateral Load Resisting System; Steel Plate Shear Wall; Vertical Boundary Element